Фінансове забезпечення місцевого самоврядування України й Польщі: реалії та перспективи - Кулай, Аліна Василівна; Гром, Василь Андрійович; Grom, V. A.; Kulaj, A. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано науково-практичні аспекти фінансового забезпечення місцевого самоврядування в Україні та Польщі. Запропоновано шляхи й механізми застосування в Україні досвіду організації бюджетно-фінансової діяльності місцевого самоврядування Польщі. Under consideration is the state of the financial security of the local government in Ukraine and Poland. It was found that the main disadvantages of self-government and the financial system of Ukraine is the uncertainty distribution of legislative powers between territorial communities of villages, towns, cities and the executive, characterized by excessive centralization of power and the budget in the state budget of Ukraine. Examined the positive aspects of the financial security of local Polish governments and methods for their use in Ukraine.
The Financial Security of the Local Government in Ukraine and Poland: Realities and Prospects
Keywords: місцеве самоврядування; місцеві бюджети; міжбюджетні відносини; доходи та видатки бюджетів; гміна; повіт; воєводство; local government; local budgets; relations budget; revenue and expenditure budgets; commune; district; province